Ecobatik: Inovasi Karya Tekstil Melalui Kolaborasi Teknik Ecoprint Daun Jati dan Batik Tulis - Utari Anggita Shanti; Nahrowi - (LPPM STIKI Malang, 2025)
The globaliation of textile products has brought ecoprint techniques from Autralia to Indonesia. Ecoprint techniques have quickly gained popularity because the material used are considered environmentally friendly. Meanwhile, hand-drawn batik, one of the tevtile crafts that has become a symbol of Indonesian culture continues to be eroded by globalization, both in terms of motifs and usage. Through thus method of creating artwork, innovation in combining ecoprint and hand-drawin batik is expected to provide a compromise in preserving cilture. Teak leaves were chosen as the main material for ecoprinting because they are abudant and spread throught Indonesia. Therefore the Ecobatik technique discovered in this stydy can provide a new source of inspiration for the development of the batik industry. Three Ecobatik works were produced in this study and can be further developed using other plant species.